T02. Impairment of consciousness induced by electrical cortical stimulation: Under-reported phenomenon or a disease-specific condition?. (May 2018) - Quraishi, Imran; Benjamin, Christopher; Spencer, Dennis D.; Blumenfeld, Hal; Alkawadri, Rafeed
Abstract : Introduction: Although consciousness is commonly impaired in epileptic seizures, limited literature is available on loss of consciousness induced by electrical cortical stimulation (ECS) in humans undergoing intracranial EEG evaluations for localization of epileptic focus. Methods: Case-study and review of literature. Results: We report a case of impairment of consciousness (IOC) induced by electrical cortical stimulation (ECS) of homologous regions within the lateral frontal convexities in a patient with medically intractable epilepsy. The patient had mixed features of idiopathic generalized and focal epilepsy. On intracranial EEG recording, interictal and ictal discharges showed a high degree of synchrony across widespread bilateral fronto-parietal areas. We identified regions in the lateral frontal lobes that reliably and produced loss of consciousness by ECS. This was accompanied by evoked EEG activity of admixed frequencies over the fronto-parietal, mesial frontal and temporal regions during stimulation and was not associated with after-discharges. Symptoms were immediately reversible upon cessation of stimulation. This finding suggests that focal cortical stimulation can disrupt widespread networks that underlie consciousness. Individuals with high degrees of speculated thalamo-frontal cortical connectivity might be more susceptible to this effect, and the findings highlight the importance of standardizing the testing of level of consciousness during mapping sessions. Conclusion: This report highlights the importance of testing for impairment of consciousness during sessions of electrical cortical stimulation. It also underlines the possibility that localized stimulation in some cases may produce widespread changes in brain physiology and in consciousness. Future prospective studiesmay elucidate the occurrence and prognostic value of impairment of consciousness during electrical cortical stimulation for mapping function.